A mutual authentication security scheme for mobile NFC devices - Chengyu ZHANG; Rangding WANG; Ling YAO; Songyin FU; Fuqiang ZUO (Dianxin kexue)
Near field communication (NFC) is a kind of short-range wireless communication technology which has been applied around the world.The applications of mobile payments and access control are the most common applications of NFC technology.Technically,the NFC device can be used as a bank card or an entrance card with the help of the card emulation mode of NFC,which will be validated by external reader.It is very essential to select a appropriate and safe certification scheme in this scenario.First of all,the existing NFC authentication system and security scheme was introduced and the system security requirements and potential security risks were analyzed.Then,by using Hash,AES and password Key dynamic updating mechanism,a mutual authentication security scheme for mobile NFC devices was proposed,and the synchronization mechanism was designd.Finally,GNY logic was used to prove the security correctness of our proposed scheme.The security analysis shows that our scheme can avoid a number of attacks,such as forgery,replay attack,eavesdropping,tampering attack,asynchronous attack and so on.